The impact of psychological contract processes on job alienation - an exploratory study of the opinions of a sample of workers at the University of Karbala - Ahmed Kazem Press,; Bashar Abbas Hussein, (Iraqi Journal for Administrative Sciences, 2025)
The current research aims to examine the impact of the relationship between psychological contract processes and functional alienation through a sample of workers in the University of Karbala reached (60) employees. It is assumed that this research staff knows the state of the psychological contract breach leads to the emergence of cases of violation of the psychological contract that will lead to the emergence of a state of alienation among workers career. The data were collected by using a questionnaire, and the use of the bath analysis way for the purpose of testing interactive relations intermediate model premise proposed regression analysis and correlation. The researchers concluded that among other conclusions psychological contract processes (breach and violation) are associated positively with the feeling of working alienation career, and that feeling of violation of the psychological contract increases the strength of the relationship between breach and a sense of alienation career. In the light of the conclusions there ware group of recommendations